Synthesis of 3-(3,4-diacetoxyphenyl)acrylic acid and 4-(oxo-3-(piperidin-1-yl)pro-1-en-1-yl)-1,2-phenylendiacetate from 3-(3,4-dihydroxyphenyl)acrylic acid and their toxicity test by Brine Shrimp Lethality Test method - Musrifah Tahar; Nunuk Hariani Soekamto (Hasanuddin University, 2023)
Derivatization 3-(3,4-dihydroxyphenyl)acrylic acid to 3-(3,4-diacetoxyphenyl)acrylic acid (1) and 4-(oxo-3-(piperidin-1-yl)pro-1-en-1-yl)-1,2-phenylendiacetate (3) and its toxicity test has been successfully carried out. Derivatization was carried out through acetylation, chlorination, and amidation reactions. The acetylation reaction was carried out using acetic anhydride in pyridine solvent at room temperature for 4 hours to produce compound 1 as a white amorphous solid with m.p. 181-183oC and yield of 85.68%. The chlorination reaction was carried out using thionyl chloride in toluene solvent at the reflux temperature of 79°C for 4 hours and continued with in situ amidation using piperidine in dichloromethane solvent at room temperature to produce compound 3 as a white crystal with m.p. 139-141oC and yield of 39.45%. The toxicity test of the two compounds against Artemia salina Leach shrimp larvae using probit analysis showed that compounds 1 and 3 were toxic with LC50 values ​​of 8.919 μg/mL and 84.511 μg/mL, respectively. This data shows that the acetylation of 3-(3,4-dihydroxyphenyl)acrylic acid compound (LC50 = 46.50 μg/mL) increases the toxicity to larvae of Artemia salina Leach shrimp. Keywords: 3-(3,4-dihydroxyphenyl)acrylic acid, 3-(3,4-diacetoxyphenyl)acrylic acid, 4-(oxo-3-(piperidin-1-yl)pro-1-en-1-yl)-1,2-phenylendiacetate, Artemia salina Leach.